PENGARUH KNOWLEDGE, SKILL DAN ATTITUDE TERHADAP KINERJA KARYAWAN CV DEWA GUPTA - Saadah, Nur; Mulyati, Awin; Nasution, Ute Ch (Research Journal of Social Science and Economics, 2025)
In the current 4.0 era, various aspects of life have changed and developed rapidly as well as companies that continue to evolve due to changes in terms of technology use, demand, needs and various other aspects. A company can function effectively and efficiently thanks to the support of its human resources, one of which is the competence factor. If an employee's performance is good, for example, and his work is successful to a high level, then the employee's performance is also good. This study used causal associative research using a quantitative approach. The variables in this study are the variables of Knowledge, Skill, Attitude towards Employee Performance of CV Dewa Gupta Sidoarjo.By using the population of all employees of CV Dewa Gupta Sidoarjo totaling 55 people and determining the sample using saturated samples. Data was collected from respondents using questionnaires by giving directly to respondents. Then the data analysis method used is multiple linear regression and processed using the SPSS statistical program version 26. Based on the determination test (R2), where the R2 result is 0.738, this shows that the variables Knowledge, Skill, and Attitude affect 73.8% of the Employee Performance variable. The variables of Knowledge, Skill, and Attitude simultaneously (together) affect CV Employee Performance according to the results of the F test. By Dewa Gupta Sidoarjo.companies should consistently develop knowledge related to the work of their employees so that knowledge and information related to their work can be conveyed optimally, companies should consistently learn new skills or work methods for their staff, and also companies should to change the behavior of its employees towards colleagues.